Implementasi Kaidah al-Masyaqqah Tajlibu al-Taisīr dalam Penggunaan Softlens sebagai Alat Bantu Penglihatan: Implementation of the Rule of al-Masyaqqah Tajlibu al-Taisīr in the Use of Softlens as a Visual Aid - Syamsiah Nur; Zulfiah Sam; Wahyuni Syam Nur Hornai (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to know and understand the use of softlens as a visual aid according to the rule of al-masyaqqah tajlibu al-taisῑr. This research uses descriptive qualitative (non-statistical) research using the library research method (literature review) which focuses on the study of manuscripts and texts, using normative and sociological approaches. The results found that the rule of al-masyaqqah tajlibu al-taisῑr is one of the foundations for a mukallaf who experiences difficulties to get a solution to the difficulty. The original law of using softlens is permissible because the purpose of its creation is as a visual aid and the use of softlens is recommended because minus sufferers with high levels can no longer use glasses so they switch to softlens. However, in applying this rule, the convenience must not bring greater harm than the previous harm. This research is expected to be a reference, literature or consideration for academia, health and become a positive reference material and information for the community, especially related parties who use contact lenses.